Artikulasi Nalar Kekerasan dalam Beragama (Analisis Kultural Film Televisi “Azab”) - Rose Kusumaning Ratri (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2024)
FTv “Azab” is one of the programs broadcast by Indosiar television station. The broadcast brought pro and contra arguments which were represented through the Panasonic Gobel Award as well as a warning from the Indonesian Broadcasting Commission (KPI). Explicitly, this television film shows scenes of violence. This raises the problem of whether violent reasoning is something that is dominant in humans and makes a major contribution in shaping one's motivation and pious behavior. Research informants are students of IAINU Kebumen. Data collection techniques were carried out through Focus Group Discussions, in-depth interviews, and observations. By applying the encoding-decoding theory of Stuart Hall and Michel Foucault's discourse perspective, this study concludes that violent reasoning does not always exist in religious practice and forms a pious attitude. Non-violent reasoning can even deny the presence of violent discourses. To obtain non-violent reasoning, one must obtain the support of knowledge and experience that becomes a framework for thinking and acting.